Development and evaluation of pH sensitive semi-interpenetrating networks: assessing the impact of itaconic acid and aloe vera on network swelling and cetirizine release - Ajaz, Nyla; Bukhsh, Munnaza; Kamal, Yousaf; Rehman, Fauzia; Irfan, Muhammad; Khalid, Syed Haroon; Asghar, Sajid; Rizg, Waleed Y.; Bukhary, Sahar M.; Hosny, Khaled M.; Alissa, Mohammed; Safhi, Awaji Y.; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Hydrogels are crosslinked three-dimensional networks, and their properties can be easily tuned to target various segments of gastrointestinal tract (GIT). Cetirizine HCl (CTZ HCl), an antihistaminic drug which when given orally, can upset the stomach. Moreover, this molecule has shown maximum absorption from intestine. To address these issues, we developed pH responsive semi-interpenetrating polymer network (semi-IPN) for delivery of CTZ HCl to lower part of GIT. Initially, ten different formulations of itaconic acid-grafted-poly(acrylamide)/aloe vera (IA-g-poly(AAm)/ aloe vera) semi-IPN were developed by varying the concentration of IA and aloe vera by free radical polymerization technique. Based on swelling and sol-gel analysis, formulation F5 containing 0.3 %w/w aloe vera and 6 %w/w IA was chosen as optimum formulation. Solid-state characterization of optimized formulation (F5) revealed successful incorporation of CTZ HCl in semi-IPN without any drug-destabilizing interaction. In vitro drug release from F5 showed limited release in acidic media followed by controlled release in intestinal environment over 72 hours. Furthermore, during in vivo evaluation, formulation F5 did not affect the hematological parameters, kidney, and liver functions. Clinical observations did not reveal any signs of illness in rabbits treated with hydrogels. Histopathological images of vital organs of treated animals showed normal cellular architecture. Thus, the results suggest non-toxic nature and overall potential of developed formulation as targeted drug carrier.